A Qualitative Exploration of Millennial Motivation in Community-Engaged Lifestyle Change Activities with #SalingSilang - Mirana Hanathasia; Annisa Fitriana Lestari; Ken Ayuthaya Purnama; Adelia Putri Maharani (RSF Press, 2024)
Participation in the community is key to motivating lifestyle changes in adolescents. Some narrative personal essays show that adolescents have great motivation to commit to specific issues, being part of the community and achieving their goals, and desire meaningful collaboration. #SalingSilang is one of Lyfe With Less’s campaigns in Indonesia to support minimalism lifestyle changes and promote inspiration, motivation, and knowledge for the community. #SalingSilang is a campaign to exchange or give free decluttered items to other participants. However, the decision to change lifestyle and interact with individuals from different backgrounds is not easy. With the #SalingSilang campaign, the authors explore the motives of members and their forms of involvement in the community. We conducted an in-depth interview to collect the main data and used semi-structured interviews with guides from Maslow’s Motivation Theory and the CDC’s nine principles of community engagement. Inductive open coding in thematic analysis was used for data analysis. For validity testing, this research used data source triangulation by not only interviewing four different members but also the founder of Lyfe With Less. It has been shown that community members are encouraged by various motivations, such as: increasing opportunities to expand relationships and developing their ideas about situations and conditions related to issues. The results also show that the dominant need is self-actualization needs. Four main themes emerged related to community engagement: self-determination, partnership, collaboration, and capacity development.